The Lombardy Emergency Medical System Faced with COVID-19: The Impact of Out-of-Hospital Outbreak. (17th October 2020) - Fagoni, Nazzareno; Perone, Giovanna; Villa, Guido Francesco; Celi, Simone; Bera, Paola; Sechi, Giuseppe Maria; Mare, Claudio; Zoli, Alberto; Botteri, Marco
Abstract: Objective: The Lombardy region was among the areas most affected by COVID-19 infection worldwide; the Lombardy Emergency Medical System (EMS) responded immediately to this emergency. We analyzed several critical aspects to understand what occurred in that region. Methods: This retrospective study compares the events managed by the dispatch center and the characteristics of the patients transported to the hospital -age, sex, SpO2, deaths- managed by the EMS in Brescia and Bergamo provinces between March-April 2020 and March-April 2019. Ambulances' waiting time at the hospitals before discharging patients and the patients' severity at emergency department admission were also analyzed. Results: EMS managed 37, 340 events in March-April 2020, +51.5% versus 2019. "Breathing" or "Infective" events reported to the dispatch center increased more than ten-fold (OR 25.1, p < 0.0001) in March 2020 and two-fold in April 2020 compared to 2019 (OR 3, p < 0.0001). Deaths increased +246% (OR 1.7, p < 0.0001), and patients not transported to hospital +481% (OR 2.9, p < 0.0001) in March 2020 compared to 2019. In some hospitals, ambulances waited more than one hour before discharging the patients, and the emergency departments doubled the admission of critically ill patients. Transported patients for "Breathing" or "Infective" events were primarily males (OR 1.5, p < 0.0001). The patients had lower SpO2 in 2020 than in 2019 and they were younger. Conclusions: The Lombardy region experienced an unexpected outbreak in an extremely short timeframe and in a limited area. The EMS coped with this pandemic, covering an extremely higher number of requests, with a ten-fold increase in the number of events managed.